PENGELOLAAN BLT DANA DESA DALAM PENANGGULANGAN DAMPAK COVID-19 DI KEPENGHULUAN BAGAN BHAKTI KECAMATAN BALAI JAYA KABUPATEN ROKAN HILIR TAHUN 2020 - Aidil Febriadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The government has diverted part of the village fund budget for BLT in order to deal with the economic impact of the COVID-19 pandemic. Village Fund BLT is distributed in two waves. Each wave consists of three stages. The first batch was given in April (phase I), May (stage II), and June (stage (III). The objectives of writing this thesis are: First, to find out how the Village Fund BLT is managed in overcoming the impact of COVID-19 at Kepenghuluan Bagan Bhakti, Balai Jaya District, Rokan Hilir Regency. Second, to find out the factors that hinder the distribution of Village Fund BLT in overcoming the impact of COVID-19 in the Penghuluan Bagan Bhakti District, Balai Jaya District, Rokan Hilir Regency. This research is a qualitative research. This research was conducted at Kepenghuluan Bagan Bhakti, Balai Jaya District, Rokan Hilir Regency. The techniques used to collect data in this study were (1) Interview, (2) Observation, and (3) Documentation. The conclusions of this study indicate that the Village Fund BLT Management implemented by the Kepenghuluan Bagan Bhakti government, Balai Jaya District, Rokan Hilir Regency is in accordance with applicable laws and regulations, starting from the planning stage to accountability. Even though the management of the Village Fund is very good, the community's understanding of the Village Fund policy is still low. The author suggests that the Head of Penghuluan needs to carry out socialization and introduction related to policies regarding the BLT DD program to the community, and related to procedures for managing Village Fund BLT to village officials, so that the community and village officials have adequate knowledge of managing Village Funds in accordance with applicable laws and regulations. Keywords: Management, Village Fund BLT, COVID-19